THE ROLE OF DIGITAL INFRASTRUCTURE, ICT SKILLS AND ICT ACCESS IN ENHANCING LABOR PRODUCTIVITY IN INDONESIA - Melinda Dwi Erda Wilianti; I Wayan Suparta; Arivina Ratih Yulihar Taher (ZILLZELL MEDIA PRIMA, 2025)
This study aims to analyze the influence of information and communication technology skills, access to information and communication technology (ICT access), and investment in BTS tower construction infrastructure on labor productivity in Indonesia during the period 2017 to 2023. The data used in the form of data panels from 34 provinces in Indonesia were analyzed using the panel data regression method. The results of the study show that ICT access and investment in BTS tower construction have a positive and significant effect on labor productivity. However, ICT skills do not show a statistically significant influence. The independent variables together are able to explain 99% of the changes in labor productivity in Indonesia. These findings affirm the importance of developing infrastructure and equitable access to ICT as the key to increasing productivity, as well as the need to improve the quality of education and training to strengthen the digital skills of the workforce. This research provides policy recommendations to accelerate the development of digital infrastructure and ICT capability improvement programs to support national productivity growth